The Aesthetics of Silence and Nonverbal Performance in the Kuwaiti Film “The Beast of the Wedding Fire”: An Approach to Visual Expression (Al-Academy, 2026)
This study aims to explore the aesthetics of silence and non-verbal performance in the Kuwaiti film Monster of the Wedding Fire (Wahsh Urs al-Nar), as a representative model of the evolution of cinematic language in visual expression beyond spoken dialogue. The research proceeds from the premise that silence in cinema does not signify the absence of speech, but rather embodies an intensified semantic presence that transcends words to express emotion and meaning through image, gesture, and movement. The study adopts a semiotic-analytical approach to examine the visual discourse of the film, focusing on how lighting, color, camera movement, body language, and editing are employed to generate psychological and aesthetic meanings that enrich the viewer’s visual experience. The findings reveal that the film presents a distinctive use of silence as a central dramatic element—serving as a medium for articulating the characters’ inner conflicts rather than mere pauses in dialogue. Moreover, the study demonstrates that the actors’ non-verbal performances play a crucial role in constructing meaning through bodily expression and visual sign systems, lending the film a contemplative tone that conveys tension and emotional depth without relying on speech. The director successfully transforms the silent space into an aesthetic field of expression and revelation, where visual signs interact with rhythmic sound and the film’s score to create a narrative structure grounded in suggestive tension rather than verbal storytelling. The study concludes that Monster of the Wedding Fire represents a pioneering experience in modern Kuwaiti cinema, affirming the artistic and expressive power of silence and non-verbal performance as aesthetic tools that redefine the relationship between image and meaning in cinematic expression.Keywords: Silence, non-verbal performance, visual aesthetics, Monster of the Wedding Fire.